A new stock-price bubble with stochastically deflating trajectories - Benedikt Rotermann; Bernd Wilfling (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
We propose a new, rational stock-price bubble that is able to generate recurringly explosive and stochastically deflating trajectories. Our flexible bubble process entails stock-price volatility dynamics that are consistent with real-world data. To demonstrate this, we fit our bubble specification to NASDAQ data and analyze the volatility dynamics.
Keywords: C1; G1; 330